Maternal Gut Inflammation Aggravates Acute Liver Failure Through Facilitating Ferroptosis via Altering Gut Microbial Metabolism in Offspring - Caijun Zhao; Lijuan Bao; Ruping Shan; Yihong Zhao; Keyi Wu; Shan Shang; Haiqi Li; Yi Liu; Ke Chen; Naisheng Zhang; Cong Ye; Xiaoyu Hu; et al. (Advanced Science, 2025)
Abstract Microbial transmission from mother to infant is important for offspring microbiome formation and health. However, it is unclear whether maternal gut inflammation (MGI) during lactation influences mother‐to‐infant microbial transmission and offspring microbiota and disease susceptibility. In this study, it is found that MGI during lactation altered the gut microbiota of suckling pups by shaping the maternal microbiota in the gut and mammary glands. MGI‐induced changes in the gut microbiota of suckling pups lasted into adulthood, resulting in the exacerbation of acute liver failure (ALF) caused by acetaminophen (APAP) in offspring. Specifically, MGI reduced the abundance of Lactobacillus reuteri (L. reuteri) and its metabolite indole‐3‐acetic acid (IAA) level in adult offspring. L. reuteri and IAA alleviated ALF in mice by promoting intestinal IL‐22 production. Mechanistically, IL‐22 limits APAP‐induced excessive oxidative stress and ferroptosis by activating STAT3. The intestinal abundances of L. reuteri and IAA are inversely associated with the progression of patients with ALF. Overall, the study reveals the role of MGI in mother‐to‐infant microbial transmission and disease development in offspring, highlighting potential strategies for intervention in ALF based on the IAA‐IL‐22‐STAT3 axis.